2016
DOI: 10.36469/9814
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Burden of Cost in Chronic Graft-versus-Host Disease: A Human Capital Approach

Abstract: With advances in organ matching and preventing acute graft-versus-host-disease (aGvHD), chronic graft-versus-host disease (cGvHD) following allogeneic hematopoietic stem cell transplantation (HSCT) has become a focus of transplant-related morbidity and mortality. Given that cGvHD often presents years following a transplant, our objective was to estimate its burden of cost resulting from allogeneic HSCT based on published estimates of incidence, morbidity, the value of lost work time and survivorship. Our choic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Moreover, a longitudinal study in the United States showed that, among patients who had undergone HSCT, only 41% of patients with cGVHD had returned to work by the third year of follow-up compared with 95% of patients without cGVHD [ 16 ]. Similarly, a sensitivity analysis in the United States on the loss of wages and productivity in patients with all cases of cGVHD showed that only 37.5% of these patients would ever return to work [ 28 ]. Of those studied, 75% of patients would be expected to fully recover and only lose 3 years of earnings, the remaining 25% would each lose 20 years of earnings because of permanent disability [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, a longitudinal study in the United States showed that, among patients who had undergone HSCT, only 41% of patients with cGVHD had returned to work by the third year of follow-up compared with 95% of patients without cGVHD [ 16 ]. Similarly, a sensitivity analysis in the United States on the loss of wages and productivity in patients with all cases of cGVHD showed that only 37.5% of these patients would ever return to work [ 28 ]. Of those studied, 75% of patients would be expected to fully recover and only lose 3 years of earnings, the remaining 25% would each lose 20 years of earnings because of permanent disability [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a sensitivity analysis in the United States on the loss of wages and productivity in patients with all cases of cGVHD showed that only 37.5% of these patients would ever return to work [ 28 ]. Of those studied, 75% of patients would be expected to fully recover and only lose 3 years of earnings, the remaining 25% would each lose 20 years of earnings because of permanent disability [ 28 ]. Again, showing similar findings on the impact of work, a recent questionnaire study by the North American cGVHD Consortium (Canada and United States) assessed the insurance, employment, and financial challenges endured by patients with cGVHD who had undergone HSCT [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations